Biomass ash as supplementary cementitious material (SCM). (24th October 2015) - Salvo, M.; Rizzo, S.; Caldirola, M.; Novajra, G.; Canonico, F.; Bianchi, M.; Ferraris, M.
Abstract : This paper describes the research done in order to valorise the biomass ash and evaluate its use as supplementary cementitious material (SCM) in the cement industry. The biomass ash samples used in this study were collected from three different power plants. The characterisation of the ashes as SCMs was performed after two different valorisation processes: (i) a vitrification process in order to obtain a new material with high hydraulicity and (ii) an easy de-alkalisation process in order to reduce the alkali content. The results of this work show that biomass ash derived from the combustion of woodchips and straw, properly treated, is characterised by pozzolanic activity and latent hydraulicity that could be exploited for the manufacture of low embodied energy concrete. The ultimate strength of mortars prepared using vitrified biomass ash becomes higher than that of the parent Portland cement after 28 days.